Associação de Trichoderma harzianum, bioativadores e interferência da umidade do solo no controle de Sclerotinia sclerotiorum na cultura do feijão - Alcamim, Thaniê Gomes (2019)
White mold, etiological agent Sclerotinia sclerotiorum, is largely disseminated around the world, being one of the main diseases of the bean plant. Trichoderma harzianum mold species shows results as an antagonist agent of S. sclerotiorum, but its association with com bioactivators and soil moisture are factors that must be evaluated in order to improve its stabilization and e propitiate greater effectiveness in biocontrol. The purpose of the work was to evaluate the interference of soil moisture in the moment of T. harzianum application and its association with bioactivators in the control of S. sclerotiorumin bean plant culture. The experiment was conducted in experimental field and in laboratories of Federal Technological University of Paraná, Dois Vizinhos Campus, in the period of august to november, 2018. The experimental design utilized was the Completely Randomised Design, with six treatments and four repetitions. The treatments were control (no application), T. harzianum isolated and in association with bioactivators, all the treatments being associated with high or low soil moisture. 50 sclerosis were packed in naylon sachets (10x8 cm) and accommodated above the soil and under the straw. The T. harzianum(Ecotrich®) biocontrol was applied in the dose of 200 liters/ha on phenological stage V6 and the bioactivator utilized was in the dose of 300ml/ha (Moss). After 20 days from the application, the sclerodian were collected and forwarded to lab for micelogenic and carpogenic evaluation. The tested variables were: germinated scleroderms percentage; number of apothecia; average amount of apothecia per sclerotia. The results show that the application of biological control agent Trichoderma harzianumin high soil moisture conditions contributes to the effectiveness in Sclerotinia sclerotiorumcontrol. The use of Trichoderma harzianumin association with bioactivator improves the performance of the biocontrol over S. sclerotiorum.